2019
DOI: 10.13052/ejcm2642-2085.2851
|View full text |Cite
|
Sign up to set email alerts
|

Stress Analysis by Two Cuboid Isoparametric Elements

Abstract: The finite element method is a powerful tool for solving most of the structural problems. This technique has been used extensively, since the complexity of the elastic field equations does not allow the specialist to find analytical solutions, especially for the three-dimensional structures. It is well-known that the finite element formulation yields the approximate stress responses. To remedy this defect, the Airy stress function is utilized in this study. The stress function formulation leads to a valid solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It is assumed that vertical cracks have appeared in the beam under the first stage of loading, thus the positive tensile stress in the concrete can be ignored [27], but the tensile effect of steel fibers needs to be considered and the tensile stress provided by the steel fibers is simplified into a rectangular distribution diagram, as shown in Figure 2, and the equilibrium relationship of the internal forces by the diagram, there are: In Equations ( 1), ( 2), F is x The equilibrium force in the direction, M is the equilibrium bending moment; η 1 and η 2 are the internal force arm factor; τ 1 is the shear stress in the precast beam at h y , σ f t is the equivalent tensile stress in the precast beam steel fibers, b is the width of the beam, h 01 is the beam height.…”
Section: Stress Analysis Of Sfrp Beam Sectionmentioning
confidence: 99%
“…It is assumed that vertical cracks have appeared in the beam under the first stage of loading, thus the positive tensile stress in the concrete can be ignored [27], but the tensile effect of steel fibers needs to be considered and the tensile stress provided by the steel fibers is simplified into a rectangular distribution diagram, as shown in Figure 2, and the equilibrium relationship of the internal forces by the diagram, there are: In Equations ( 1), ( 2), F is x The equilibrium force in the direction, M is the equilibrium bending moment; η 1 and η 2 are the internal force arm factor; τ 1 is the shear stress in the precast beam at h y , σ f t is the equivalent tensile stress in the precast beam steel fibers, b is the width of the beam, h 01 is the beam height.…”
Section: Stress Analysis Of Sfrp Beam Sectionmentioning
confidence: 99%
“…Wang et al [ 13 ] studied the seismic response of an unequal-span subway station under different site conditions and presented the distribution of structural tensile damage and its variation rule with site conditions. Rezaiee-Pajand et al [ 14 – 18 ] suggested several new types of finite element and analytical methods that can be used for dynamic and damage analysis of underground structures. Shirkhani et al [ 19 23 ] studied the seismic damping systems for structures and evaluated their effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental analysis obtained that the inter-ply slip phenomenon occurs when the inter-ply shear stress of asphalt pavement under tire action is greater than its inter-ply shear strength, resulting in an inter-ply slip on the pavement surface and leading to slip cracks in the surface layer. Jon A. Epps et al [22][23][24][25]. Summarized a large number of actual cases to conclude that the areas prone to slip cracking such as airports and highways often have large shear stresses, and pointed out that the main cause of slip cracking is the shear strength of the interlayer interface.…”
Section: Introductionmentioning
confidence: 99%